All‐Weather Solar Cells: A Rising Photovoltaic Revolution. Issue 34 (3rd May 2017) - Tang, Qunwei
Abstract: Solar cells have been considered as one of the foremost solutions to energy and environmental problems because of clean, high efficiency, cost‐effective, and inexhaustible features. The historical development and state‐of‐the‐art solar cells mainly focus on elevating photoelectric conversion efficiency upon direct sunlight illumination. It is still a challenging problem to realize persistent high‐efficiency power generation in rainy, foggy, haze, and dark‐light conditions (night). The physical proof‐of‐concept for all‐weather solar cells opens a door for an upcoming photovoltaic revolution. Our group has been exploring constructive routes to build all‐weather solar cells so that these advanced photovoltaic technologies can be an indication for global solar industry in bringing down the cost of energy harvesting. How the all‐weather solar cells are built without reducing photo performances and why such architectures can realize electricity outputs with no visible‐light are discussed. Potential pathways and opportunities to enrich all‐weather solar cell families are envisaged. The aspects discussed here may enable researchers to develop undiscovered abilities and to explore wide applications of advanced photovoltaics. Abstract : Come rain or shine ! All‐weather solar cells would trigger a photovoltaic revolutionary. In this article, we have outlined the design principles, working mechanisms, photovoltaic structures, proof‐of‐concepts experimental performances as well as potential pathways to all‐weather solar cells.